ANALISIS DISKRIMINAN FAKTOR-FAKTOR YANG MEMPENGARUHI INDEKS PRESTASI KUMULATIF MAHASISWA PENDIDIKAN MATEMATIKA UNIVERSITAS HKBP NOMMENSEN MEDAN - Depari, Victory; Simanjuntak, Ruth Mayasari; Simbolon, Lolyta Damora (Universitas Quality, 2024)
The Cumulative Grade Point Average (GPA) is used in higher education to measure how well students perform in their studies. Mathematics Education students have varying GPAs each semester due to various factors. The aim of this study is to determine the type of discriminant function, or discriminant model, and identify the components that significantly influence the GPA of Mathematics Education students at HKBP Nommensen University. Another goal is to assess the accuracy of the discriminant function classification. This study involved 50 active students from the Mathematics class of 2020, 2021, and 2022. The sample was taken using a simple random sampling technique, and the research type used was quantitative, as the results are in numerical form and will be analyzed quantitatively using discriminant analysis. The research method employed is also quantitative. Based on the results, a discriminant model was obtained that describes the factors influencing the GPA of Mathematics Education students, with the equation: Y= 0.119 + 6.138X₄ + 8.120X₆ -13.910X₉. The variables that significantly affect GPA are learning motivation, mental health, and campus environment. This discriminant model can classify students with 100% accuracy, allowing it to be used to determine whether a student has a GPA below 3.75 or above/equal to 3.75.